Empowerment of women: the impact of BRAC's rural development programme - Banu, Dilruba; Farashuddin, Fehmin; Hossain, Altaf; Akter, Shahnuj (BRAC, 2019)
The paper conceptualizes empowerment as a continuous process o/change that is greatly influenced by the length of time a woman has been involved in BRAC. Women's participation in economic activities, and ownership and control over assets have been increased due to their investment in BRAC, though they cannot take independent decisions in many cases. They have begun to acquire positive self-perceptions of their own personal interests. Their economic dependence on husbands and other male kin for personal and household expenses decreases over time. BRAC involvement has had positive impacts on women's mobility to some extent. Finally, there is an improvement in their relationships with their husbands.